Pengaruh Tekanan, Kesempatan, Rasionalisasi, dan Kemampuan terhadap Kecurangan Laporan Keuangan: Studi Empiris BUMN yang Terdaftar di BEI Tahun 2018-2020 - Izzati, Annisa Nurul; Syofyan, Efrizal (Universitas Negeri Padang, 2023)
This research is that aims to investigate the effects of diamond fraud elements (pressure, opportunity, rationalization, and capability) on detected fraudulent financial reporting. This study provide the influence of the pressure proxied by financial stability, external pressure, and financial target, the opportunity proxied by nature of industry, the rationalization proxied by change in auditor, and the capability proxied by change in director. The test is performed by using multiple linear regression on the 60 data samples of BUMN on Indonesia Stock Exchange in the period 2018-2020. In line with there was R2 of 0,829 or 82,9%. It mean the contribution from pressure, opportunity, rationalization, and capability is 82,9% while the rest of 17,1% was explained by other variables outside the research. The results show that financial target variable proved to be significantly positive have an effect on fraudulent financial reporting, while external pressure and change in auditor variable proved to be significantly negative, and financial stability, nature of industry, and change in director had no effect on fraudulent financial statements.